Can digital transformation enhance labor productivity in enterprises: An analysis from the perspective of business process reengineering - Yi Zhou; Jialun Lyu; Li Li (PLoS ONE, 2025)
From the perspective of business process reengineering, this paper analyzes the impact of digital transformation on labor productivity in enterprises and its underlying mechanisms. The study finds that digital transformation significantly enhances labor productivity in enterprises, with both the application of digital technologies and innovation in digital technology scenarios having a notable positive effect. Furthermore, digital transformation improves labor productivity mainly by optimizing production management processes, reducing human resource redundancy, enhancing the efficiency of human resource utilization, and improving internal control mechanisms to enhance decision-making efficiency. The effects of digital transformation on labor productivity are more pronounced in non-state-owned enterprises and enterprises that are highly dependent on their industrial chains. Further analysis shows that the level of industry monopoly and the overall digitalization level of the industry play a moderating role in the process by which digital transformation affects labor productivity.